Sharing vocabularies: towards horizontal alignment of values-driven business functions - Painter-Morland, Mollie; Pouryousefi, Sareh; Hibbert, Sally; Russon, Jo-Anna (Springer, 2018)
This paper highlights the emergence of different ‘vocabularies’ that describe various values-driven business functions within large organisations and argues for improved horizontal alignment between them. We investigate two established functions that have long-standing organisational histories: Ethics and Compliance (E&C) and Corporate Social Responsibility (CSR). By drawing upon research on organisational alignment, we explain both the need for and the potential benefit of greater alignment between these values-driven functions. We then examine the structural and socio-cultural dimensions of organisational systems through which E&C and CSR horizontal alignment can be coordinated to improve synergies, address tensions, and generate insight to inform future research and practice in the field of Business and Society. The paper concludes with research questions that can inform future scholarly research and a practical model to guide organizations’ efforts towards inter-functional, horizontal alignment of values-driven organizational practice.